Análise dos impactos socioambientais da construção de barragens para a geração de energia por hidrelétricas - o caso da usina de Belo Monte - PA. - Brilhante, Tairine de Sousa (Universidade Federal Rural do Semi-Árido, 2018)
The current energy scenario has reflected the constant search for new generation technologies that cause as little damage as possible to the environment.The use of hydropower is an alternative for the production of clean and sustainable energy. However, the environmental and social impacts caused by the construction of the reservoir are numerous and need to be considered. In this sense, the present work constitutes an analysis of the socio-environmental impacts of the construction of dams for electric power generation, focusing on the case of the Belo Monte Hydroelectric Plant in the state of Pará. Through the review and analysis of materials published by various authors, it aims to evaluate this type of work on the perspective of its vast consequences and to point out the main advantages, as well as its disadvantages. The results demonstrate that the construction of the Belo Monte Power Plant drastically impacted the society life of the cities located around the Xingu River, due to failures in the design and execution of the Environmental Impact Study carried out by Norte Energia. The damage ranges from the eviction of thousands of families and indigenous groups, who lost their right to their memories and life histories, until the death of tons of fish that impacted the lives of fishermen and river dwellers who had fishing as their main source of livelihood. In this perspective, alternative energies such as biomass, wind and solar are much more advantageous in relation to hydraulics with regard to the environmental impacts generated. These have enormous potential for generation to be studied and implemented.
Monografia
Keywords: Meio ambiente; Environment; Impactos sociais; Social Impacts; Energia alternativa; Alternative Energies; Energia elétrica; Electricity; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA